Inside Cover: Metal–Organic‐Framework‐Templated Polyelectrolyte Nanocapsules for the Encapsulation and Delivery of Small‐Molecule–Polymer Conjugates (Chem. Asian J. 12/2016). Issue 12 (15th June 2016) - Liu, Shuo; Chen, Jianbin; Bao, Xiaojia; Li, Tao; Ling, Yunyang; Li, Chunxiang; Wu, Chuanliu; Zhao, Yibing
Abstract : Nanoscale metal–organic frameworks are exploited as templates for the fabrication of layer‐by‐layer polyelectrolyte nanocapsules. As small‐molecule drugs or imaging agents cannot be efficiently encapsulated by polyelectrolyte nanocapsules, two polymers (i.e., comb‐shaped and hyperbranched polyethylene glycol) were used for the conjugation of model drugs and imaging agents, which were then encapsulated inside the nanocapsules. Additionally, it was systematically examined how the encapsulation efficiency and release kinetics of the conjugates can be controlled by varying the composition and architectures of the polymers. More information can be found in the Full Paper by Chuanliu Wu, Yibing Zhao, and co‐workers onpage 1811 in Issue 12, 2016 (DOI:10.1002/asia.201600250 ).